Study on compliance to abduction brace in treatment of clubfoot using ponseti method - Mohd Fakhri, Mohd Zaini (2014)
Introduction Management of idiopathic clubfoot since the last decade have been through Ponseti method. It has been proven worldwide to be an effective treatment in correcting the deformity approaching 98%. This study was conducted to find the success rate for Ponseti method of treatment in HUSM and the compliance rate of abduction bracing. This study was also design to find any association between success rate of Ponseti treatment and compliance to abduction bracing. It also look into whether number of cast required and age of presentation influence the compliance. Methods This retrospective study was conducted on 32 CTEV patients with 40 feet treated at HUSM from January 2008 to June 2012. All of these patients were treated using Ponseti method comprising of corrective serial casting, tenotomy and abduction bracing. The patients feet were reassessed using 2 scoring systems (Pirani and MHJDF) to asses success rate. Parents were given questionnaire to asses compliance to abduction bracing. Result The mean age of presentation was at 28.5 days (12-120) where the mean cast applied for correction was 6 casts (45%). Thirty one feet (77.5%) were compliant to the bracing protocol and 9 feet (22.5%) did not. Success rate was measured in feet with good outcome in patients who followed the Ponseti method and compliance to abduction brace. Success rate in the compliant group for this study was 100%. However, good outcome for the non-compliant group was 55.6%. The chi-square test had proven statistically that there is a significant association between the outcome and compliance to the abduction brace protocol. Conclusion The success rate for treatment of idiopathic CTEV with Ponseti method in HUSM is 100%. The compliance rate to abduction bracing was 77.5%. This study had proven statistically that there was an association between outcome and compliance with abduction bracing.